The Usefulness of Morphology in Diagnosing various Malignancies on Bone Marrow Examination in Adults- A Single Centre Study - Nazia Khalid , Attika Khalid , Lubna Zafar , Nadia Arif , Mehmood ul Hasan (Journal of Rawalpindi Medical College, 2020)
Introduction: Bone marrow is the site of involvement of various neoplasms. The objective of this study was to determine the incidence of various malignancies (Haematological and non-Haematological) in adults diagnosed on morphological examination of bone marrow. Materials and Methods: It was a single-centre, retrospective study conducted at the Department of Pathology, Fauji Foundation Hospital, Rawalpindi from January 2012 to December 2018. All patients above 15 years of age diagnosed as having Haematological or Non-Haematological malignancy involving bone marrow were included in the study. Data was analyzed using SPSS version 17. Results: A total of 275 adult patients had malignancies involving bone marrow; 233 (84.7%) were females and 42 (15.3%) were males. Out of 275 patients, 50 (18.1%) patients had Acute Myeloid Leukaemia, 45 (16.3 %) had Chronic Myeloid Leukaemia (CML), 41 (14.9 %) having Non-Hodgkin lymphoma (NHL), 32 (11.6 %) having Acute Lymphoblastic Leukaemia (ALL), 31 (11.2 %) having Chronic Lymphocytic Leukaemia (CLL) and 27 (9.8 %) having Plasma cell Myeloma. Metastatic infiltrates were seen in 16 (5.8 %) patients. Myeloproliferative neoplasms (MPN) in 6 (2.1%), Essential Thrombocythaemia in 5 (1.8 %), Polycythaemia vera in 4 (1.4%), Primary myelofibrosis in 2 (0.7 %), Hodgkins Lymphoma in 2 (0.7 %), and Plasma Cell Leukaemia in 1 (0.3 %) patient were seen. Thirteen (4.7%) patients of Acute leukaemia and 6 (2.1%) patients of MPN required further testing by Immunophenotyping/Cytogenetics for a conclusive diagnosis. Conclusion: Leukaemias were the most common malignancies involving bone marrow, followed by Non-Hodgkin Lymphomas, Plasma cell myeloma and Metastatic infiltrates. Morphology by light microscopy remains the single most useful tool for the diagnosis of malignancies, especially in under-resourced centres.